A Palladium on Carbon Catalyzed One-Pot Synthesis of Substituted Benzimidazoles - Joardar, Soumen; Bhattacharyya, Anjan; Das, Saktipada (Synthesis, 2014)
A new and efficient palladium on carbon catalyzed one-pot intramolecular nitro reduction/cyclization reaction has been developed for the preparation of a series of substituted benzimidazoles, including some novel ring-fused [1,2-a]-tricyclic, [1,2-a]-tetracyclic, and chiral benzimidazoles. The main advantages of this method are the mild and simple reaction conditions, the easy isolation of the products, and the excellent yields. The reaction has the potential to be used as a general procedure for the preparation of 7-aminobenzimidazoles in good yields. A plausible mechanism for the reaction is proposed.
Keywords: heterocycles; reductions; cyclizations; catalysis; palladium; one-pot reactions